Synergistic effects of deposits and sulfate reducing bacteria on the corrosion of carbon steel. (1st May 2022) - Yang, J.; Wang, Z.B.; Qiao, Y.X.; Zheng, Y.G.
Abstract: The synergistic effects of deposits and sulfate reducing bacteria (SRB) on the corrosion of a carbon steel are clarified by purposely designing four groups of experiments. The weight loss combined with electrochemical measurements and the surface profiling determine quantitatively that deposits and SRB contribute synergistically 75% and 49% to uniform and localized corrosion, respectively. Based on the experimental evidence, the synergism is explained in terms of the promotion effects of SRB on under-deposit corrosion (UDC) due to unevenly distributed iron sulfides produced by SRB and the acceleration effects of deposits on SRB corrosion resulting from UDC-induced accumulation of SRB. Highlights: Deposits and SRB are found to synergistically promote corrosion of carbon steel. The accumulation of SRB in deposits is experimentally proved. Synergism is ascribed to SRB accumulation in deposits and SRB-produced sulfides.